Pediatric rigid bronchoscopy and foreign body removal during the COVID-19 pandemic: case report - Darren Jonathan Leitao; Jodi L. P. Jones (Journal of Otolaryngology - Head and Neck Surgery, 2020)
Abstract We present the case of an eight year old boy who presented with foreign body aspiration during the COVID-19 pandemic. The patient was taken the operating room for rigid bronchoscopy and foreign body removal. The details of the operation, steps taken for protection of health care workers, and lessons learned are discussed. Bronchoscopy was performed using N95 respirators and Stryker Flyte Hood garments, combined with a streamlined instrument set-up. Simulation in advance of these cases improves communication and operative planning. Surgeons should have equipment to retrieve foreign bodies from the oropharynx available. Techniques that reduce surgical time and thus exposure risk should be considered.